2012
DOI: 10.1111/odi.12017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodontal therapy on disease activity and systemic inflammation in rheumatoid arthritis patients

Abstract: Non-surgical periodontal treatment may prove beneficial in reducing RA severity as measured by ESR, CRP, TNF-α levels in serum and DAS28 in low or moderate to highly active RA patients with chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
2
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 44 publications
(89 reference statements)
11
76
2
19
Order By: Relevance
“…Other studies [2932] have suggested that nonsurgical periodontal therapy improves rheumatoid arthritis parameters, including a recent study showing reductions in erythrocyte sedimentation rate/C-reactive protein, tumor necrosis factor (TNF) levels, and Disease Activity Score. Though not designed to address a periodontal hypothesis, a rheumatoid arthritis treatment study [33] with doxycycline with methotrexate (MTX) showed that 20 mg/day doxycycline (the dose typically used to treat periodontal disease) had similar ACR50 responses as a 100-mg dose; both doses were superior to placebo–MTX.…”
Section: Association Studies Between Periodontal Disease and Rheumatomentioning
confidence: 99%
“…Other studies [2932] have suggested that nonsurgical periodontal therapy improves rheumatoid arthritis parameters, including a recent study showing reductions in erythrocyte sedimentation rate/C-reactive protein, tumor necrosis factor (TNF) levels, and Disease Activity Score. Though not designed to address a periodontal hypothesis, a rheumatoid arthritis treatment study [33] with doxycycline with methotrexate (MTX) showed that 20 mg/day doxycycline (the dose typically used to treat periodontal disease) had similar ACR50 responses as a 100-mg dose; both doses were superior to placebo–MTX.…”
Section: Association Studies Between Periodontal Disease and Rheumatomentioning
confidence: 99%
“…110 More recent treatment studies confirm these findings, with a significant decrease in TNF-a levels. [119][120][121] Improvement in signs and symptoms of RA occurred, regardless of whether the RA patients were under anti-TNF-a treatment. 117 Anti-TNF-a RA treatment had no effect on the periodontal health without periodontal therapy.…”
Section: Rheumatoid Arthritismentioning
confidence: 95%
“…Additional longitudinal studies are therefore needed to establish a role for PD in RA pathogenesis. Intriguingly, however, treating PD appears to improve RA severity and concomitantly decrease pro-inflammatory biomarkers of disease activity such as CRP, ESR, TNF, and IL-1beta [3738]. RA patients with active PD are also less responsive to anti-TNF-α inhibition, indicating a potential role for the co-treatment of PD in TNF refractory patients [39].…”
Section: Evidence For the Ra-periodontal Disease Associationmentioning
confidence: 99%